Strategi Komunikasi Indonesia Memperkuat Posisi sebagai Pusat Gaya Busana Muslim Global - Yusuf, Ramayani; Haerani , Hanni; Yulianita, Neni (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Indonesia has long been known as one of the centers of the global Muslim fashion industry. This research analyzes communication strategies that Indonesia can implement to strengthen its position in the international Muslim fashion scene. Using a qualitative approach, the research was conducted through literature studies, in-depth interviews with stakeholders in the Muslim fashion industry , and analysis of creative industry development policies. The research results identify five main communication strategies: (1) developing the narrative "Indonesia as the World Center of Muslim Fashion" through cultural and fashion diplomacy; (2) strengthening collaboration between the government, designers, and industry players; (3) optimizing digital platforms (4) organizing international Muslim fashion events (5) empowering Muslim fashion SMEs through training and access to global markets.  This research provides a strategic framework for the development of Indonesia's Muslim fashion industry and the strengthening of its position on the global Muslim fashion map. The implementation of well-planned and coordinated communication strategies will support the achievement of Indonesia's vision